Legal Regulation of Economic Processes at the Macro Level - M. N. Semyakin; A. V. Gubareva; S. P. Stepkin (Vestnik MGIMO-Universiteta)
The article analyzes the legal regulation of the economy at the structural level. Economists usually ignore the impact of law on macroeconomic processes. The main attention is paid to the study of the legal regulation of economic relations at the level of macroeconomics, as well as its primary links enterprises, organizations, etc. In particular, the legal regulation of several sublevels of the economy is singled out and considered: reproductive, sectoral (intersectoral), regional (interregional). It is concluded that the system of economic management is constantly undergoing changes under the influence of various factors of an objective and subjective nature, an important place among which is occupied by legal means and methods. The ideas put forward by R. Coase need to be reconsidered, considering new economic realities. Recommendations are made aimed at strengthening the role of the contract in economic management, improving legislation, and eliminating excessive administration of the activities of economic entities.